Tik-tok as a modern marketing tool in the digital economy - Prykhodko, E. G.; Pererva, P. G. (My University, 2023)
Tik-tok is justified by its short playback, low creation threshold and strong user commitment to content that meets fragmented consumer demand. The short clip uses the dynamic image and sound mode, its freedom in the form of distribution makes it popular among users. Currently, the distribution of short videos for mobile devices is in line with the characteristics of the growing number of users and the growth of the consumer market.
Tik-tok як сучасний маркетинговий інструмент у цифровій економіці
Keywords: marketing; social networks; tik tok; advertising; market; demand; supply